Laboratory diagnostics of murine blood for detection of mouse cytomegalovirus (MCMV)-induced hepatitis. Issue 1 (December 2018) - Stahl, Felix; Jung, Roman; Jazbutyte, Virginija; Ostermann, Eléonore; Tödter, Silvia; Brixel, Renke; Kemmer, Annette; Halle, Stephan; Rose-John, Stefan; Messerle, Martin; Arck, Petra; Brune, Wolfram; et al.
Abstract Mouse models are important and versatile tools to study mechanisms and novel therapies of human diseasein vivo . Both, the number and the complexity of murine models are constantly increasing and modification of genes of interest as well as any exogenous challenge may lead to unanticipated biological effects. Laboratory diagnostics of blood samples provide a comprehensive and rapid screening for multiple organ function and are fundamental to detect human disease. Here, we adapt an array of laboratory medicine-based tests commonly used in humans to establish a platform for standardized, multi-parametric, and quality-controlled diagnostics of murine blood samples. We determined sex-dependent reference intervals of 51 commonly used laboratory medicine tests for samples obtained from the C57BL/6J mouse strain. As a proof of principle, we applied these diagnostic tests in a mouse cytomegalovirus (MCMV) infection model to screen for organ damage. Consistent with histopathological findings, plasma concentrations of liver-specific enzymes were elevated, supporting the diagnosis of a virus-induced hepatitis. Plasma activities of aminotransferases correlated with viral loads in livers at various days after MCMV infection and discriminated infected from non-infected animals. This study provides murine blood reference intervals of common laboratory medicine parameters and illustrates the use of these tests for diagnosis of infectious disease in experimental animals.